KHIND: electric iron / Nur Syahida Kamarulbahri - Kamarulbahri, Nur Syahida (2022)
This assignment is to identify the problem with the product. The company I chose is KHIND company. Out of their range of products, I have chosen the Electric Iron EI228T to do my analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the Electric Iron EI228T. The main problem I identified on this Electric Iron EI228T is water always drips out of the soleplate of the iron. Based on the problem, I can find the best solution which is the steam iron must have a self-cleaning function that cleans out any build up with a strong blast of steam and can prevent from dripping.